In vivo dynamics and anti-tumor effects of EpCAM-directed CAR T-cells against brain metastases from lung cancer - Tao Xu; Philipp Karschnia; Bruno Loureiro Cadilha; Sertac Dede; Michael Lorenz; Niklas Seewaldt; Elene Nikolaishvili; Katharina Müller; Jens Blobner; Nico Teske; Julika J. Herold; Kai Rejeski; et al. (OncoImmunology)
Lung cancer patients are at risk for brain metastases and often succumb to their intracranial disease. Chimeric Antigen Receptor (CAR) T-cells emerged as a powerful cell-based immunotherapy for hematological malignancies; however, it remains unclear whether CAR T-cells represent a viable therapy for brain metastases. Here, we established a syngeneic orthotopic cerebral metastasis model in mice by combining a chronic cranial window with repetitive intracerebral two-photon laser scanning-microscopy. This approach enabled in vivo-characterization of fluorescent CAR T-cells and tumor cells on a single-cell level over weeks. Intraparenchymal injection of Lewis lung carcinoma cells (expressing the tumor cell-antigen EpCAM) was performed, and EpCAM-directed CAR T-cells were injected either intravenously or into the adjacent brain parenchyma. In mice receiving EpCAM-directed CAR T-cells intravenously, we neither observed substantial CAR T-cell accumulation within the tumor nor relevant anti-tumor effects. Local CAR T-cell injection, however, resulted in intratumoral CAR T-cell accumulation compared to controls treated with T-cells lacking a CAR. This finding was accompanied by reduced tumorous growth as determined per in vivo-microscopy and immunofluorescence of excised brains and also translated into prolonged survival. However, the intratumoral number of EpCAM-directed CAR T-cells decreased during the observation period, pointing toward insufficient persistence. No CNS-specific or systemic toxicities of EpCAM-directed CAR T-cells were observed in our fully immunocompetent model. Collectively, our findings indicate that locally (but not intravenously) injected CAR T-cells may safely induce relevant anti-tumor effects in brain metastases from lung cancer. Strategies improving the intratumoral CAR T-cell persistence may further boost the therapeutic success.